SOCIALIZATION OF UMKM UP GRADE AND HALAL CERTIFICATION CHAMBER OF COMMERCE & INDUSTRY (KADIN) SIDOARJO - EAST JAVA: SOSIALISASI UMKM NAIK KELAS DAN SERTIFIKASI HALAL KAMAR DAGANG & INDUSTRI (KADIN) SIDOARJO - JAWA TIMUR - handayani, puspita (Journal of Social Comunity Services, 2024)
Upgrading Micro, Small and Medium Enterprises (MSMEs) is a concept built to develop them, so that they can increase competitiveness. Upgrading MSMEs is an indicator of increased productivity so that they are able to develop better. Halal certification is one medium that can be implemented to advance to class. Lack of information about the important role in the halal certification application process means that MSMEs are not yet motivated to apply for halal certification. In fact, a halal certificate is needed to guarantee halal products consumed by Muslims. Apart from that, a halal certificate is also required as one of the legalities of products produced by MSMEs. Therefore, outreach is needed to help MSMEs apply for halal certification. This community service activity was carried out in Sidoarjo Regency. This activity was carried out in coordination with the Sidoarjo Chamber of Commerce & Industry (KADIN). Activities are carried out through 2 (two) methods, namely the coordination stage and the socialization stage.